Landfill leachates as an abiotic disease factor affecting solanaceous crops and olive trees - Sawalha, Hazem Diab Aref; Ma’ali, Rasha; Hussein, Anan (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Different landfills in Jenin district were selected in this research, and are considered the main garbage destination for the north part of the West bank. Due to their expected drastic effect on agriculture, the experiment was carried out to study the impact of such landfills on nearby olive orchards. The results showed that the landfills since their establishment caused drastic reduction of olive production from an average of 1500 kg/hectare in 2005 to 560 kg/hectare in 2009. Furthermore, olive production in the studied area stopped absolutely in 2011 due to complete olive orchard failure. On the other hand, the effect of landfills was studied on vegetables under lab conditions. Therefore, different dilutions of the landfill leachate were used to irrigate tomato and pepper plants. The results showed that leachate caused plant stunting and reduction in leaf surface area when compared with control regardless of dilution used, but more pronounced in dilution zero. On the other hand, chlorophyll concentration was more in plant treated with zero dilution of leachate when compared with other treatments. Number of dropped leaves was more in plant treated with zero dilution of leachate when compared with other dilutions and control. The plants treated with zero dilution died before others treatments. Conclusion: leachate may have a drastic effect on nearby cultivated plant and could affect plant growth and lead to premature plant death.